Investigating the binding properties of NbC/Fe-based composite layer and HT300 through experiments and simulations - Nana Zhao; Rui Shan; Zihan Wang; Teli Yao; Congcong Ren; Heguang Liu; Shujuan Li; Yunhua Xu; Zhen Cui (Materials Research Express, 2023)
In this work, the hot-pressing diffusion method was used for the fabrication of a novel composite structure. More specifically, by keeping the temperature constant at 1000 °C and applying a pressure value of 40 MPa for 60 min, α 90 min and 120 min, respectively, the NbC/Fe composite layer on the surface of HT300 was formed. The microstructure, element distribution, microhardness, bonding property and scratch deformation characteristics of NbC/Fe composite layer were studied, and the fracture mode was studied by simulation and tensile test at the micro level. The results show that the main components of the NbC/Fe composite layer prepared in the experiment are α - Fe and NbC, the composition of the composite layer is pure. The thickness of NbC/Fe composite layer prepared with 60 min, 90 min and 120 min holding time is 5 μ m, 15 μ m and 23 μ m. The hardness of the composite layer can reach 2096.4 HV _0.1 ; The bonding property between the NbC/Fe composite layer and the matrix is the best when the heat preservation is 120 min. Because the tensile fracture is brittle and the fracture location is in the NbC/Fe composite layer, the bonding strength between the composite layer and the matrix is greater than 297MPa, which has excellent bonding properties. In the scratch test, the longer the holding time is, the stronger the bonding ability between the reinforcing layer and the matrix is, 41.2N (90 min) and 75.75N (120 min) respectively. The fracture mechanism in the NbC/Fe composite layer was simulated by abaqus. The fracture of the composite layer was caused by the propagation of microcracks caused by the stress concentration at the sharp corner of square NbC particles in the layer.